Thermomechanical factor in genesis of the transversefaults on the North-Western Caucasus - S. Y. Sergin; A. L. Reutov; A. F. Prochorenko (Известия высших учебных заведений: Геология и разведка)
The transverse deep faults are inherent for the North-Western Caucasus. Their genesis can be explained by thermo-mechanical processes on the late geosyncline-orogenic stage of the geological evolution of the district. These processes include: the cooling of the upper core, thermal contraction of the rocks, appearance of tensile stresses and ruptures in the Earth’s crust. The calculations show that inner-core opening of the cracks is from 1 to 2 meters per 1 kilometer of axis line of the orogene. The dominance of the earthquakes with hypocenters at depths of 5-15 kilometers in the investigated region corresponds to its thermos-mechanical nature.